PENGEMBANGAN MODUL BERBASIS INKUIRI TERBIMBING PADA MATERI ENERGI DAN PERUBAHANNYA KELAS IV SEKOLAH DASAR - Aprinido Alfa Kusuma; Titis Angga Rini; Fajar Maulana Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was carried out to produce a guided inquiry learning module on the topic of energy and its changes for grade IV elementary school students, with the module expected to satisfy the standards of validity, practicality, and effectiveness. A Research and Development (R&D) design following the ADDIE framework was applied, engaging 25 pupils as research subjects. Data collection combined classroom observation, teacher interviews, expert validation sheets, user response questionnaires, and a set of achievement tests. Findings indicated that the developed module obtained a validity rating of 94% from the material expert and 95% from the media expert, placing it in the very valid category. Practicality scores from teachers and pupils reached 95.6% and 93.8%, respectively, confirming a highly practical rating. The average student score rose from 61.43 to 86.57, yielding an N-Gain value of 0.65 which falls under the moderate category. Based on these results, the module can be considered a suitable resource for supporting science instruction at the elementary level.